2019
DOI: 10.1017/s0033291719002836
|View full text |Cite
|
Sign up to set email alerts
|

A role for 5-HT4 receptors in human learning and memory

Abstract: Background5-HT4 receptor stimulation has pro-cognitive and antidepressant-like effects in animal experimental studies; however, this pharmacological approach has not yet been tested in humans. Here we used the 5-HT4 receptor partial agonist prucalopride to assess the translatability of these effects and characterise, for the first time, the consequences of 5-HT4 receptor activation on human cognition and emotion.MethodsForty one healthy volunteers were randomised, double-blind, to a single dose of prucalopride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 61 publications
(82 reference statements)
4
35
0
Order By: Relevance
“…Although the current analysis focused on changes in seizure frequency and impact on everyday EF, the results cannot rule out the possibility of an additional independent mechanism of action of fenfluramine for everyday EF. It is important to note that the wellknown serotonergic effects of fenfluramine-in particular, its effects on the 5HT 4 receptor-may also play a role in the positive changes observed in EF and cognition [53][54][55]. Furthermore, preclinical studies have shown that fenfluramine has positive modulatory activity at sigma-1 receptors, which contributes to both antiseizure activity and positive effects on EF in zebrafish and mouse models [53,55].…”
Section: Discussionmentioning
confidence: 99%
“…Although the current analysis focused on changes in seizure frequency and impact on everyday EF, the results cannot rule out the possibility of an additional independent mechanism of action of fenfluramine for everyday EF. It is important to note that the wellknown serotonergic effects of fenfluramine-in particular, its effects on the 5HT 4 receptor-may also play a role in the positive changes observed in EF and cognition [53][54][55]. Furthermore, preclinical studies have shown that fenfluramine has positive modulatory activity at sigma-1 receptors, which contributes to both antiseizure activity and positive effects on EF in zebrafish and mouse models [53,55].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from rodent studies, there is an earlier report that the 5-HT 4 receptor agonist RS 17017 improved the cognitive performance in non-human primates (Terry et al, 1998). More recently in a study of healthy human volunteers, a single dose of the 5-HT 4 receptor agonist prucalopride was found to have pro-cognitive effects in a battery of learning and memory tests, although the drug was not active in models of emotional processing that have antidepressant predictive capability (Murphy et al, 2019). Although exploratory in nature, the latter study reported relatively mild adverse effects of prucalopride, in particular headache, nausea and diarrhoea, and consistent with that expected of agents with 5-HT 4 receptor agonist actions.…”
Section: -Ht 4 Receptorsmentioning
confidence: 99%
“…Therefore, the interest of 5-HT 4 R agonist have been investigated to treat depressive disorders [26]. Despite first negative results regarding prucolopride anti-depressant effects [27] several 5-HT 4 R ligands are still investigated in clinical trials including prucalopride 3, Revexepride 10 and PF-04995274 17 [26].…”
Section: -Htmentioning
confidence: 99%